2017
DOI: 10.3390/toxins9070217
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Fumonisin B2 Production by Aspergillus niger Intented Used in Food Industry in China

Abstract: There are a total of 30 strains including 27 strains of Aspergillus niger intended used in Chinese food industry, two strains used as control and one strain isolated from corn for fumonisin (FB) production on 3 media. It was found that FB2 production by A. niger was function-dependent and highly related to culture media, as well as incubation time. All strains studied were unable to produce FB1 and FB3. Almost all strains were found to produce FB2 on corn, rice and wheat bran. Based on their intended use in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…All of the four isolated strains belonging to A. niger were shown to be FB1 and FB2 producers. This finding is in good agreement with previous studies indicating that out of all species from Aspergillus section Nigri, the most potent FB1 and FB2 producer is A. niger [17][18][19][20]75]. Another possible candidate capable of producing fumonisins is A. welwitschiae [17][18][19][20]65,72].…”
Section: Ochratoxigenic and Fumonisins Production Potential Of Aspergsupporting
confidence: 92%
“…All of the four isolated strains belonging to A. niger were shown to be FB1 and FB2 producers. This finding is in good agreement with previous studies indicating that out of all species from Aspergillus section Nigri, the most potent FB1 and FB2 producer is A. niger [17][18][19][20]75]. Another possible candidate capable of producing fumonisins is A. welwitschiae [17][18][19][20]65,72].…”
Section: Ochratoxigenic and Fumonisins Production Potential Of Aspergsupporting
confidence: 92%
“…However, Aspergillus niger and its sibling species A. welwitschiae (originally named A. awamori ) also produce fumonisins of the B 2 , B 4 , and B 6 types (Frisvad et al 2007 ; 2010) and may produce fumonisins in cereals and grapes (Logrieco et al 2009 ; Mogensen et al 2010 ; Munkvold et al 2018 ). Several industrial strains have the capability to produce fumonisins (Frisvad et al 2010; Han et al 2017 ), so it is important to use strains that do not produce these mycotoxins. Current A. niger production strains have been developed that either have been selected due to the lack of fumonisin production or contain a deletion of the fumonisin gene cluster (unpublished results).…”
Section: Mycotoxins Are a Very Limited Group Of Fungal Secondary Metamentioning
confidence: 99%
“…Thirty strains of A.niger were used to survey their dynamic OTA producing profiles ( Table 1 ). Firstly, it should be noted that the culture conditions of OTA production for the strains of A.niger used in this study were the same as those of the fumonisin (FB) production which we reported previously [ 14 ]. It was found that the positive rates of OTA produced by the studied 30 strains ranged from 13.3% at day 28 to 26.7% at day 7 and day 21 on corn, 13.3% at day 7 to 30.0% at day 21 on rice, and 20.0% at day 14 and day 28 to 40.0% at day 21 on wheat bran, while the average concentrations of OTA for those strains ranged from 4.6 μg/kg at day 28 to 7.8 μg/kg at day 21 on corn, 3.8 μg/kg at day 7 to 16.2 μg/kg at day 14 on rice, and 4.1 μg/kg at day 7 to 6.5 μg/kg at day 21 on wheat bran, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the positive rates of OTA produced by the studied 30 strains ranged from 13.3% at day 28 to 26.7% at day 7 and day 21 on corn, 13.3% at day 7 to 30.0% at day 21 on rice, and 20.0% at day 14 and day 28 to 40.0% at day 21 on wheat bran, while the average concentrations of OTA for those strains ranged from 4.6 μg/kg at day 28 to 7.8 μg/kg at day 21 on corn, 3.8 μg/kg at day 7 to 16.2 μg/kg at day 14 on rice, and 4.1 μg/kg at day 7 to 6.5 μg/kg at day 21 on wheat bran, respectively. Therefore, the concentrations of OTA at different time intervals were far lower than those detected for FB 2 under the same culture conditions [ 14 ]. The maximum levels of OTA for the studied 30 strains of A.niger at all time intervals were 181.5 μg/kg for corn, 427.8 μg/kg for rice, and 175.4 μg/kg for wheat bran, while the maximum levels of FB 2 for those strains under the same culture conditions were 70,488 μg/kg for corn, 54,284 μg/kg for rice, and 38,094 μg/kg for wheat bran [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation